Linking acoustic communications and network performance. Integration and experimentation of an underwater acoustic network - Caiti, A. (2014)
Underwater acoustic networks (UANs) are an emerging technology for a number of oceanic applications, ranging from oceanographic data collection to surveillance applications. However, their reliable usage in the field is still an open research problem, due to the challenges posed by the oceanic environment. The UAN project, a European-Union-funded initiative, moved along these lines, and it was one of the first cases of successful deployment of a mobile underwater sensor network integrated within a wide-area network, which included above water and underwater sensors. This contribution, together with a description of the underwater network, aims at evaluating the communication performance, and correlating the variation of the acoustic channel to the behavior of the entire network stack. Results are given based on the data collected during the UAN11 (May 2011, Trondheim Fjord area, Norway) sea trial. During the experimental activities, the network was in operation for five continuous days and was composed of up to four Fixed NOdes (FNOs), two autonomous underwater vehicles (AUVs), and one mobile node mounted on the supporting research vessel. Results from the experimentation at sea are reported in terms of channel impulse response (CIR) and signal-to-interference-plus-noise ratio (SINR) as measured by the acoustic modems during the sea tests. The performance of the upper network levels is measured in terms of round trip time (RTT) and probability of packet loss (PL). The analysis shows how the communication performance was dominated by variations in signal-to-noise ratio, and how this impacted the behavior of the whole network. Qualitative explanation of communication performance variations can be accounted, at least in the UAN11 experiment, by standard computation of the CIR and transmission loss estimate.